Covalent organic framework material for removing nano plastic in water body, preparation method and application

The TAPB-TPA COF material prepared by ultrasonic synthesis solves the problems of metal leakage and insufficient stability of existing adsorbents in removing nanoplastics in water bodies, and achieves efficient removal of nanoplastics and good reusability.

CN119798580AActive Publication Date: 2025-04-11DALIAN UNIV OF TECH

Patent Information

Application Number
CN202510095970.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing adsorbents have metal leakage problems and insufficient stability in removing nanoplastics in water bodies, making it difficult to effectively remove nanoplastics.

Method used

The covalent organic frame material TAPB-TPA COF was prepared by ultrasonic synthesis method, and a stable covalent organic frame structure was generated through Schiff base reaction, which solved the problems of metal leakage and insufficient stability.

Benefits of technology

It has achieved efficient removal of nanoplastics in water, with the removal rate of nanoplastics up to 99%, and the material has good reusability and chemical stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119798580A_ABST
    Figure CN119798580A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of pollutant removal, and provides a covalent organic framework material for removing nano plastic in a water body as well as a preparation method and application of the covalent organic framework material. According to the preparation method, 1, 3, 5-tri (4-aminophenyl) benzene and terephthalaldehyde are taken as monomers, and the covalent organic framework material TAPB-TPA COF is prepared by adopting an ultrasonic synthesis method under the conditions of normal temperature and normal pressure. The prepared COF shows a good adsorption effect on polystyrene nano plastic in a water body, the removal rate can reach 99% within 2 h, and the maximum adsorption capacity is close to 180 mg / g. After circulation for three times, the adsorption efficiency of the COF material can still reach 80% or above, and the cyclic utilization performance is good. The removal efficiency of PSNPs in seawater can reach 97.96%, and the method has good application potential in the aspect of repairing a water body polluted by nano plastic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of environmental water pollution control, and relates to a covalent organic framework material for removing nanoplastics in water, a preparation method and an application thereof. Background Art

[0002] Plastic products are widely used in all aspects of life because of their cost-effectiveness, lightness and plasticity. However, most plastic waste is incinerated, landfilled or directly discharged into the environment. Under the influence of mechanical wear, solar radiation, natural weathering and microbial degradation, these widely distributed plastics are broken down into tiny particles, thus producing microplastics (MPs, 1μm~5mm) and nanoplastics (NPs, <1μm). Due to their unique physicochemical properties and chemical stability, micro-nanoplastics accumulate in soil, sediments, oceans, freshwater and atmospheric environments. Nanoplastics have a larger specific surface area and hydrophobicity than microplastics, and may pose stronger environmental risks. Persistent organic pollutants and heavy metals are easily adsorbed and combined with nanoplastics, increasing their toxicity, and accumulating upward along the food chain, endangering human health. When nanoplastics enter the body, they interfere with biological metabolic pathways, causing metabolic disorders in organs such as the liver, pancreas, kidneys, and intestines, leading to metabolic dysfunction (S. Haldar, Y. Muralidaran, D. Miguez, et al., Eco-toxicity of nano-plastics and its implication on human metabolism: Current and future perspective, Science of the Total Environment 861 (2023) 12.). Therefore, nanoplastic pollution has become a hot environmental issue of global concern, and removing nanoplastics from water bodies has become an urgent task to ensure water ecological safety.

[0003] As a removal technology with high efficiency, simple equipment and convenient operation, the selection of efficient adsorption materials is the core issue of adsorption method. The adsorbent needs to have high adsorption capacity, excellent chemical stability, selectivity and reusability. In recent years, polymer materials such as metal organic frameworks (MOFs) and covalent organic frameworks (COFs) have stood out from many materials due to their advantages such as easy functionalization, adjustable pores and high specific surface area. However, studies have found that since MOF is a porous material connected by ionic bonds and coordination bonds, it has poor stability in aqueous solution, the structure is easy to collapse, and metal leakage may occur during operation. The Fenton reaction triggered by the release of metal ions will produce reactive oxygen, which shows different degrees of cytotoxicity both in vitro and in vivo (QXLiu, SMKhor, Emerging absorption-based techniques for removing microplastics and nanoplastics from actual water bodies, TrAC Trends in Analytical Chemistry 170 (2024) 117465.). Therefore, in order to study adsorbents with high nanoplastic removal rate and high stability, a preparation method and application of COF materials for removing nanoplastics from water were proposed. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a covalent organic framework material, a preparation method and an application for removing nanoplastics in water. A TAPB-TPACOF material with a simple preparation method, excellent adsorption performance and reusability is obtained through ultrasonic synthesis to solve the shortcomings of existing adsorbents in removing nanoplastics.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing a covalent organic framework material for removing nanoplastics from water bodies, wherein the method uses 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde as monomers, and uses an ultrasonic synthesis method at room temperature and pressure to prepare the covalent organic framework material TAPB-TPA COF. Specifically, the method comprises the following steps:

[0007] Step (1), dispersing 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde in an organic solvent, and stirring to obtain a uniform mixed solution.

[0008] Furthermore, in the step (1), the molar ratio of terephthalaldehyde to 1,3,5-tri(4-aminophenyl)benzene is 3:2 to 3:4, and the mass concentration of 1,3,5-tri(4-aminophenyl)benzene in the mixed solution is 3.3 to 6.6 mg / mL.

[0009] Furthermore, in step (1), the organic solvent includes dimethyl sulfoxide solution, acetonitrile, and dichloromethane.

[0010] Furthermore, in step (1), the stirring time is 10 to 30 minutes.

[0011] Step (2), under ultrasonic conditions, slowly add acetic acid to the mixed solution obtained in step (1) until a yellow solid product appears, and continue stirring. The yellow solid product is washed with a detergent and then vacuum dried to obtain a TAPB-TPA COF material.

[0012] Furthermore, in step (2), 1 to 3 mL of acetic acid is added to every 32 mL of the mixed solution. The ultrasonic time is 10 to 30 minutes, and the stirring time is 30 minutes to 12 hours.

[0013] Furthermore, in the step (2), the washing agent is tetrahydrofuran and methanol, and the yellow solid product is washed with tetrahydrofuran and methanol in sequence.

[0014] Furthermore, in the step (2), the vacuum drying temperature is 55 to 75° C., and the vacuum drying time is 12 to 24 hours.

[0015] The present invention adopts Fourier transform infrared spectrometer and field emission scanning electron microscope to characterize the TAPB-TPA COF material.

[0016] Furthermore, in step (2), the structural formula of the TAPB-TPA COF material is as follows:

[0017]

[0018] An application of a covalent organic framework material for removing nanoplastics from water bodies, wherein the covalent organic framework material is used to remove nanoplastics from water bodies, and the removal rate of nanoplastics PSNPs can reach 99%. Specifically:

[0019] Step (1), adding the covalent organic framework material to water containing nanoplastics for oscillation, the dosage of TAPB-TPACOF is 0.1-0.5 g / L, the concentration of nanoplastics is 5-20 mg / L, and the adsorption time is 0.5-6 h; adding interfering ions with a concentration of 5-50 mM.

[0020] Further, the interfering ion is Na + , K + , Ca 2+ 、NO3 - 、HCO3 - 、SO4 2- and PO4 2- .

[0021] Furthermore, the nanoplastic is polystyrene, and the particle size of the nanoplastic is 70 to 110 nm.

[0022] Step (2), centrifugally separating the used TAPB-TPA COF material, adding detergent, washing and analyzing the nanoplastic, and vacuum drying to complete regeneration, the number of cycles is 1 to 3 times.

[0023] Furthermore, the detergent is anhydrous ethanol, methanol, or NaOH solution.

[0024] The beneficial effects of the present invention are:

[0025] (1) The reaction principle and innovation of the present invention are as follows: the synthesis of TAPB-TPA COF is mainly based on the Schiff base reaction, that is, through the condensation reaction between the aldehyde group and the amino group; the innovation is that the TAPB-TPA COF material prepared by the present invention solves the problem of metal leakage in the existing adsorbents, and there is no report on the removal of nanoplastics in water, and it has good application potential.

[0026] (2) The present invention adopts ultrasonic synthesis method to obtain a stable covalent organic framework structure at room temperature, which is simple to operate and takes a short preparation time. It also has the advantages of fast adsorption rate and reusability for nanoplastics. The removal rate of nanoplastic PSNPs can reach 99%. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a Fourier transform infrared spectrum (FTIR) diagram of the TAPB-TPA COF-1 material prepared in Example 1 of the present invention and the reaction ligands TAPB and TPA.

[0028] Figure 2 Scanning electron microscope (SEM) images of the TAPB-TPA COF-1 material prepared in Example 1 of the present invention before and after adsorption of PSNPs.

[0029] Figure 3 This is the removal rate of PSNPs by TAPB-TPA COF-1 with different dosages prepared in Example 1 of the present invention.

[0030] Figure 4 This is the removal effect of TAPB-TPACOF-1 prepared in Example 1 of the present invention on PSNPs in the presence of interfering ions.

[0031] Figure 5 The reusability of TAPB-TPACOF-1 prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below by embodiments in combination with the accompanying drawings. However, it is necessary to point out that the following embodiments are only used to describe the content of the present invention, and are not intended to limit the scope of the present invention in any way. Based on the embodiments of the present invention, other examples obtained by other technicians in the field without departing from the theory of the present invention all belong to the protection scope of the present invention.

[0033] Example 1

[0034] A method for preparing a covalent organic framework material for removing nanoplastics from water, comprising the following steps:

[0035] (1) At room temperature and pressure, add 32 mL of dimethyl sulfoxide solution to a conical flask. Weigh 106 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and disperse it in the solution. Then weigh 60 mg of terephthalaldehyde (TPA) and add it to the conical flask and stir for 10 minutes. The molar ratio of TPA to TAPB is 3:2.

[0036] (2) Under ultrasonic conditions (ultrasonication for 10 min), 1 mL of acetic acid (99.5%) was slowly added dropwise to the above solution until a yellow precipitate appeared, and stirring was continued for 30 min.

[0037] (3) The yellow solid product was washed with tetrahydrofuran and methanol (the pore size of the filter membrane was 0.22 μm) in sequence, and then vacuum dried at 55°C for 12 h. The obtained material was named TAPB-TPACOF-1 material. It was sieved using a 26-mesh screen to obtain a solid adsorbent with a size of less than 700 μm.

[0038] Structural characterization of TAPB-TPACOF-1 material:

[0039] The surface structure and morphology of the TAPB-TPA COF-1 prepared in Example 1 were characterized by Fourier transform infrared spectrometer and field emission scanning electron microscope, respectively. Figure 1 The FTIR analysis of the reaction ligands TAPB and TPA and the TAPB-TPA COF-1 material in Example 1 shows that the TPA monomer has a peak at 1694 cm -1 The characteristic peak at 3433cm -1 、3353cm- 1and 3208cm -1 The characteristic peak at 1515cm is the stretching vibration peak of NH. -1 The absorption peaks at 1499 cm -1 The absorption peaks at 1621 cm-1 are all C=C stretching vibration peaks. With the significant weakening of the C=O stretching vibration peak of TPA and the NH characteristic peak of TAPB, the absorption peaks at 1621 cm-1 of TAPB-TPACOF-1 are all C=C stretching vibration peaks. -1 A new characteristic peak belonging to C=N stretching vibration appears at , indicating that the amino group of TAPB and the aldehyde group of TPA successfully undergo Schiff base reaction to generate an imine bond, confirming that the present invention successfully prepares TAPB-TPA COF-1 material.

[0040] The microstructure of the TAPB-TPA COF material prepared in Example 1 was observed by SEM. Figure 2 As shown in a. TAPB-TPA COF-1 materials aggregated together to form large aggregates with irregular shapes and pores. This irregular and rough surface may provide a large number of adsorption sites for the removal of PSNPs.

[0041] Example 2

[0042] A method for preparing a covalent organic framework material for removing nanoplastics from water bodies, comprising the following steps:

[0043] (1) At room temperature and pressure, add 32 mL of acetonitrile solution to a conical flask. Weigh 159 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and disperse it in the solution. Then weigh 60 mg of terephthalaldehyde (TPA) and add it to the conical flask and stir for 20 minutes. The molar ratio of TPA to TAPB is 3:3.

[0044] (2) Under ultrasonic conditions (ultrasonication for 20 min), 2 mL of acetic acid (99.5%) was slowly added dropwise to the above solution until a yellow precipitate appeared, and stirring was continued for 3 h.

[0045] (3) The yellow solid product was washed with tetrahydrofuran and methanol (the pore size of the filter membrane was 0.22 μm) in sequence, and then vacuum dried at 65°C for 18 h. The obtained material was named TAPB-TPA COF-2 material. It was sieved with a 26-mesh screen to obtain a solid adsorbent with a size of less than 700 μm.

[0046] Structural characterization of TAPB-TPACOF-2 materials:

[0047] The surface structure of TAPB-TPA COF-2 prepared in Example 2 was analyzed by Fourier transform infrared spectrometer. -1The characteristic peak at 3433cm -1 、3353cm- 1 and 3208cm -1 The characteristic peak at 1515cm is the stretching vibration peak of NH. -1 The absorption peaks at 1499 cm -1 The absorption peaks at 1621 cm-1 of TAPB-TPACOF-2 are all C=C stretching vibration peaks. With the significant weakening of the C=O stretching vibration peak of TPA and the NH characteristic peak of TAPB, the absorption peaks at 1621 cm-1 of TAPB-TPACOF-2 are all C=C stretching vibration peaks. -1 A new characteristic peak belonging to C=N stretching vibration appears at , indicating that the amino group of TAPB and the aldehyde group of TPA successfully undergo Schiff base reaction to generate an imine bond, confirming that the present invention successfully prepares TAPB-TPA COF-2 material.

[0048] Example 3

[0049] A method for preparing a covalent organic framework material for removing nanoplastics from water, comprising the following steps:

[0050] (1) At room temperature and pressure, add 32 mL of dichloromethane solution to a conical flask. Weigh 212 mg of 1,3,5-tris(4-aminophenyl)benzene (TAPB) and disperse it in the solution. Then weigh 60 mg of terephthalaldehyde (TPA) and add it to the conical flask and stir for 30 minutes. The molar ratio of TPA to TAPB is 3:4.

[0051] (2) Under ultrasonic conditions (ultrasonication for 30 min), 3 mL of acetic acid (99.5%) was slowly added dropwise to the above solution until a yellow precipitate appeared, and stirring was continued for 6 h.

[0052] (3) The yellow solid product was washed with tetrahydrofuran and methanol (the pore size of the filter membrane was 0.22 μm) in sequence, and then vacuum dried at 75°C for 24 h. The obtained material was named TAPB-TPACOF-3 material. It was sieved with a 26-mesh screen to obtain a solid adsorbent with a size of less than 700 μm.

[0053] Structural characterization of TAPB-TPA COF-3 materials:

[0054] The surface structure and morphology of TAPB-TPACOF-3 prepared in Example 3 were characterized by Fourier transform infrared spectrometer and field emission scanning electron microscope. -1 The characteristic peak at 3433cm -1 、3353cm- 1 and 3208cm -1The characteristic peak at 1515cm is the stretching vibration peak of NH. -1 The absorption peaks at 1499 cm -1 The absorption peaks at 1621 cm-1 of TAPB-TPACOF-3 are all C=C stretching vibration peaks. With the significant weakening of the C=O stretching vibration peak of TPA and the NH characteristic peak of TAPB, the absorption peaks at 1621 cm-1 of TAPB-TPACOF-3 are all C=C stretching vibration peaks. -1 A new characteristic peak belonging to C=N stretching vibration appears at , indicating that the amino group of TAPB and the aldehyde group of TPA successfully undergo Schiff base reaction to generate an imine bond, confirming that the present invention successfully prepares TAPB-TPACOF-3 material.

[0055] Example 4

[0056] Application of a covalent organic framework material for removing nanoplastics from water:

[0057] The TAPB-TPACOF-1 prepared in Example 1 is used as an adsorbent to study the removal performance of the material of the present invention on nanoplastics. The steps are as follows:

[0058] (1) Determine the optimal dose of adsorbent

[0059] The dosages of TAPB-TPA COF-1 were 0.1 g / L, 0.3 g / L and 0.5 g / L, respectively. The concentration of nanoplastics in the water to be treated was 10 mg / L. The removal efficiency of PSNPs by TAPB-TPACOF-1 at different dosages was as follows: Figure 3 As shown. The larger the dosage, the shorter the time to reach adsorption equilibrium, which may be because more TAPB-TPA COF-1 materials can provide more adsorption sites. When the dosage of TAPB-TPA COF-1 is 0.1g / L, the adsorption process is slow as time increases, and it takes 6h to reach adsorption equilibrium. When the dosage of TAPB-TPACOF-1 is 0.3 and 0.5g / L, the adsorption rate is significantly improved, and it can reach more than 90% in 1h. After 1h, the adsorption performance of 3mg COF and 5mg COF is close. Therefore, the optimal dosage of TAPB-TPA COF-1 is 0.3g / L.

[0060] In addition, the SEM images after adding PSNPs are shown in Figure 2 As shown in b, PSNPs with regular shapes were attached to the surface of TAPB-TPACOF-1, proving that TAPB-TPA COF-1 successfully adsorbed PSNPs.

[0061] (2) Influence of interfering ions

[0062] In order to explore the effect of adsorbent on the removal of nanoplastics when other ions exist in the solution, TAPB-TPACOF-1 was added to the solution containing Na + , K + , Ca 2+ 、NO3 - 、HCO3 - 、SO4 2- and PO4 2- of PSNPs solution.

[0063] like Figure 4 As shown in the figure, the removal rate of PSNPs after adding different ions. + , K + , Ca 2+ , Cl - and SO4 2- When 5 mM Na3PO4 was present in the solution, the removal efficiency of PSNPs by TAPB-TPACOF-1 was only 21%, indicating that HCO3 - and PO4 3- There is a significant inhibitory effect on the removal of PSNPs by TAPB-TPACOF-1.

[0064] (3) Impact of environmental samples

[0065] In order to evaluate the adsorption capacity of TAPB-TPA COF-1 for PSNPs in actual environmental samples, the present invention selects river water, sewage and seawater as environmental samples. The three water samples were filtered separately using a 0.22 μm filter membrane to remove impurities in the water. A PSNPs solution with a concentration of 10 mg / L was prepared using a pretreated water sample for adsorption experiments. In seawater, the removal rate of PSNPs can reach 97.96%. In river water and sewage, the removal rate decreased slightly, but it can still reach 85%. Compared with river water and sewage, seawater has a higher salinity and total dissolved solids, which makes PSNPs more easily destabilized and aggregated, which is conducive to adsorption. The above results show that TAPB-TPA COF-1 has the ability to repair environmental samples.

[0066] Example 5

[0067] Application of a covalent organic framework material for removing nanoplastics from water:

[0068] The TAPB-TPA COF-1 prepared in Example 1 is used as an adsorbent to study the ability of the material of the present invention to reuse nanoplastics. The steps are as follows:

[0069] The used TAPB-TPA COF-1 material is separated by centrifugation, anhydrous ethanol solution is added, the nanoplastic is washed and analyzed, and vacuum drying is performed to complete regeneration, and the number of cycles is 1 to 3 times.

[0070] like Figure 5 As shown in the figure, after TAPB-TPA COF-1 is recycled once, its removal rate can still reach 99%. After 3 cycles, TAPB-TPACOF-1 material maintains a high removal efficiency and can remove more than 80% of PSNPs in the solution. In addition, FTIR analysis found that the molecular structure of the adsorbent after each washing with anhydrous ethanol has hardly changed, indicating that it has excellent recycling regeneration ability.

[0071] Example 6

[0072] Application of a covalent organic framework material for removing nanoplastics from water:

[0073] The TAPB-TPA COF-1 prepared in Example 1 is used as an adsorbent to study the ability of the material of the present invention to reuse nanoplastics. The steps are as follows:

[0074] The used TAPB-TPACOF-1 material is separated by centrifugation, and a methanol solution is added to wash and analyze the nanoplastics, and the nanoplastics are regenerated by vacuum drying, and the number of cycles is 1 to 3 times.

[0075] Example 7

[0076] Application of a covalent organic framework material for removing nanoplastics from water:

[0077] The TAPB-TPA COF-1 prepared in Example 1 is used as an adsorbent to study the ability of the material of the present invention to reuse nanoplastics. The steps are as follows:

[0078] The used TAPB-TPA COF-1 material is separated by centrifugation, and a NaOH solution is added to wash and analyze the nanoplastics, and the nanoplastics are regenerated by vacuum drying, and the number of cycles is 1 to 3 times.

[0079] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. For those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A method for preparing a covalent organic framework material for removing nanoplastics from water, characterized in that: The preparation method uses 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde as monomers, and adopts ultrasonic synthesis method to prepare the covalent organic framework material TAPB-TPA COF under normal temperature and pressure conditions; specifically includes the following steps: Step (1), dispersing 1,3,5-tri(4-aminophenyl)benzene and terephthalaldehyde in an organic solvent, and stirring to obtain a uniform mixed solution; Step (2), under ultrasonic conditions, slowly add acetic acid to the mixed solution obtained in step (1) until a yellow solid product appears, and continue stirring; wash the yellow solid product with a detergent, and vacuum dry it to obtain a TAPB-TPACOF material.

2. The method for preparing a covalent organic framework material for removing nanoplastics in water according to claim 1, characterized in that: In the step (1), the molar ratio of terephthalaldehyde to 1,3,5-tris(4-aminophenyl)benzene is 3:2 to 3:4; and the mass concentration of 1,3,5-tris(4-aminophenyl)benzene in the mixed solution is 3.3 to 6.6 mg / mL.

3. The method for preparing a covalent organic framework material for removing nanoplastics in water according to claim 1, characterized in that: In the step (1), the organic solvent includes dimethyl sulfoxide solution, acetonitrile or dichloromethane; in the step (1), the stirring time is 10 to 30 minutes.

4. The method for preparing a covalent organic framework material for removing nanoplastics in water according to claim 1, characterized in that: In the step (2), 1 to 3 mL of acetic acid is added to every 32 mL of the mixed solution; the ultrasonic time is 10 to 30 min, and the stirring time is continued for 30 min to 12 h.

5. The method for preparing a covalent organic framework material for removing nanoplastics in water according to claim 1, characterized in that: In the step (2), the washing agent is tetrahydrofuran and methanol, and the yellow solid product is washed with tetrahydrofuran and methanol in sequence; in the step (2), the vacuum drying temperature is 55 to 75° C., and the vacuum drying time is 12 to 24 hours.

6. A covalent organic framework material for removing nanoplastics from water, characterized in that: The TAPB-TPACOF material is prepared by the preparation method according to any one of claims 1 to 5, and the structural formula of the TAPB-TPACOF material is as follows:

7. An application of the covalent organic framework material for removing nanoplastics in water according to claim 6, characterized in that: The covalent organic framework material is used to remove nanoplastics in water.

8. The use of a covalent organic framework material for removing nanoplastics in water according to claim 7, characterized in that: When applied, the removal rate of nanoplastic PSNPs can reach 99%. The specific application process is: Step (1), adding the covalent organic framework material to water containing nanoplastics for oscillation, wherein the dosage of TAPB-TPA COF is 0.1-0.5 g / L, the concentration of nanoplastics is 5-20 mg / L, and the adsorption time is 0.5-6 h; adding interfering ions with a concentration of 5-50 mM; Step (2), centrifugally separating the used TAPB-TPA COF material, adding detergent, washing and analyzing the nanoplastic, and vacuum drying to complete regeneration, the number of cycles is 1 to 3 times.

9. The use of a covalent organic framework material for removing nanoplastics in water according to claim 8, characterized in that: In the step (1): the interfering ion is Na + , K + , Ca 2+ 、NO3 - 、HCO3 - 、SO4 2- and PO4 2- ; The nano plastic is polystyrene, and the particle size of the nano plastic is 70 to 110 nm.

10. The use of a covalent organic framework material for removing nanoplastics in water according to claim 8, characterized in that: In the step (2), the detergent is anhydrous ethanol, methanol or NaOH solution.

Citation Information

Patent Citations

  • Covalent organic framework film material for removing triclosan in environmental water as well as preparation method and application of same

    CN111647184A

  • Nitrogen-rich covalent organic framework material as well as preparation method and application thereof

    CN117603422A

  • Preparation method for and use of covalent organic framework material for co 2 desorption

    WO2024119699A1

Cited By

  • Super-hydrophobic composite filler for bioretention facility as well as preparation method and application of super-hydrophobic composite filler

    CN121288790A

  • A super-hydrophobic composite filler for a bioretention facility and a preparation method and application thereof

    CN121288790B